2006
DOI: 10.1074/mcp.m500298-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Comparison of Rat Mitochondria from Muscle, Heart, and Liver

Abstract: Mitochondria, through oxidative phosphorylation, are the primary source of energy production in all tissues under aerobic conditions. Although critical to life, energy production is not the only function of mitochondria, and the composition of this organelle is tailored to meet the specific needs of each cell type. As an organelle, the mitochondrion has been a popular subject for proteomic analysis, but quantitative proteomic methods have yet to be applied to tease apart subtle differences among mitochondria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
232
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(247 citation statements)
references
References 37 publications
8
232
0
1
Order By: Relevance
“…Distinct proteins (553 out of 2191; or 2082 nonredundant proteins) presented in this study overlapped with the MitoP2-database, corresponding to 76% mouse mitochondrial proteome coverage. On the other hand, approximately 45% of the proteins identified by Forner et al [30] (a total of 887 proteins collected from rat tissues of muscle, heart, and liver) had an apparent orthologue against the 2004 mouse MitoP database [59]. The proteomic results of mouse brain mitochondria achieved by Kislinger et al [29] were also compared to the mitochondrial protein reference set of the MitoP2-database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct proteins (553 out of 2191; or 2082 nonredundant proteins) presented in this study overlapped with the MitoP2-database, corresponding to 76% mouse mitochondrial proteome coverage. On the other hand, approximately 45% of the proteins identified by Forner et al [30] (a total of 887 proteins collected from rat tissues of muscle, heart, and liver) had an apparent orthologue against the 2004 mouse MitoP database [59]. The proteomic results of mouse brain mitochondria achieved by Kislinger et al [29] were also compared to the mitochondrial protein reference set of the MitoP2-database.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, considerable efforts have been devoted to the application of various LC techniques in single or multidimensional separation format prior to MS detection for the analysis of mitochondrial proteins [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In particular, the peptide-based shotgun proteomic studies fully exploit the resolution and sensitivity achievable with multidimensional LC-MS or SDS-PAGE/LC-MS approaches, allowing many additional mitochondrial proteins to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to both liver and kidney, PBMC and cardiac mitochondrial function declined dramatically with reperfusion. While direct reperfusion injury with the generation of toxic reactive oxygen species and peroxynitrite may account for the acute changes seen in cardiac mitochondrial function (32,33), PBMC’s in our model were not subjected to hypoxia and the serum pO2 did not decline during hemorrhagic shock or resuscitation. Although it is unclear how resuscitation directly impairs PBMC mitochondrial function, the release of nitric oxide and IL-6 into the circulation upon reperfusion could potentially inhibit mitochondrial function directly (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of mammalian cells contain mitochondria, there is striking diversity across tissue types in terms of mitochondrial protein expression, function, and capacity for oxidative phosphorylation (32). As such, it is not surprising that the different organs in our study demonstrated a variable response to hemorrhagic shock and resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 399 mitochondrial proteins were identified, in which approximately 50% were not generally detected in all the tissues. This group implemented a quantitative proteomics approach to compare the mitochondrial proteins extracted from the rat tissues, heart, liver and skeletal muscle, and observed that approximate one third of the mitochondrial proteins identified were predominant to one of the three tissues [14]. The largest scale screening for the tissue-specific proteins of cytosol, microsomes, mitochondria and nuclei in the mouse brain, heart, kidney, liver, lung and placenta was performed using a gel-free multidimensional protein identification technology developed by Kislinger et al [15].…”
Section: Special Topicmentioning
confidence: 99%